Determinants of Price Earnings Ratio in Manufacturing Industry in Jordan - Fesokh, Ahmad; Haddad, Fayez (Jordan Journal of Business Administration, 2019)
This study aims to investigate the factors that explain the behavior of the Price/Earnings ratio, where the study’s main purpose is to establish a relationship between the Price/Earnings ratio and the factors that determine it. The study collected financial data for the period (2000 – 2013) from Amman Stock Exchange for the companies in the Jordanian manufacturing sector. The results (OLS regression) showed that Tobin’s Q, dividend growth, leverage and size had the most significant effect on the Price/Earnings ratio, where Tobin’s Q and leverage had a positive effect, indicating that the investors' confidence increases with higher firm market value and higher firm debt dependency. However, size and dividend growth had a significant, but negative, relationship with the Price /Earnings ratio.